Ship building with ROWER. - Gonzalez de Santos, P.
A four-legged mobile platform increases productivity and improves quality and working conditions for industrial naval applications. It is an automatic welding system for ship construction processes. It increases productivity by increasing total arc time, improving weld quality, and creating better working conditions for operators. The overall system consists of a commercial welding system handled by a commercial manipulator. These subsystems are carried on a mobile platform that provides mobility in the working area. A stereo vision system finds the starting and ending points of the welding seam. All four subsystems are remote-controlled by a computer supervised by an operator located off the work site. The supervisor computer also contains a database of the geometric description of each working cell
Keywords: ROWER; Automatic welding system; Database; Four-legged mobile platform; Industrial naval applications; Operator working conditions; Remote control; Ship building; Stereo vision system; Weld quality